Do monozygotic twins have identical genotypes? - Cichocka, Barbara (Anthropological Review, 1995)
Recent observation of the fertilization process and further embryonic development concerned with the fate of spermatozoon mitochondria, as well as the results of studies on genetic mechanisms of differentiation and cooperation between the nuclear and mitochondrial genomes allow to conclude that monozygotic twins do not have identical genotypes. One of the evidences is the development of hereditary diseases in only one of such twins.